Altered States: Translation and Minority Languages - Cronin, Michael (TTR, 1995)
AbstractAltered States: Translation and Minority Languages — The linguistic complexity of Europe is often ignored in political accounts of its translation practice. In particular, the historical experience and contemporary fate of European minority languages are overlooked in assessing the translation strategies available to speakers of minority languages. The problem partly results from a failure to think creatively about definitions of minority languages in a translation context. This context includes the dimension of new technologies which may lead to a new reclassification of languages in Europe and elsewhere. The role of translation in the case of one European minority language, Irish Gaelic, is considered in terms of the dilemmas faced by lesser used languages. Translation is both welcomed and feared. The options available to translators in minority languages differ crucially from those on offer to translators in majority languages. These differences need to be reflected in the theoretical discourse on translation in minority languages but this is not often the case. Furthermore, translation studies as a discipline rarely reflects on its own majority language bias, embedded in the structures of the disciplinary dissemination of knowledge. Minority languages are not only essential to a diversity that sustains the fragile ecosystem of human culture but they also raise questions that lie at the heart of translation studies as an area of intellectual inquiry.